The Stance of the Dominicans Towards the Immaculate Conception of Mary on the Example of Selected Scripts (13th-16th Centuries) - Kochaniewicz, Bogusław (My University, 2024)
This study entitled “The Stance of the Dominicans Towards the Immaculate Conception of Mary on the Example of Selected Scripts (13th16the Centuries)” aims to answer the question of how great the influence of St. Thomas’ position on the opinions of Dominican theologians regarding the analyzed issue was. It examines the negative and homogeneous position adopted by the Dominicans, revealing its foundations and the presence of the theological perspective indicated by St. Thomas Aquinas. El presente estudio, titulado “La postura de los dominicos ante la Inmaculada Concepción de María a partir del ejemplo de textos seleccionados (siglos XIII-XVI)” pretende responder a la pregunta de cuán grande fue la influencia de la postura de santo Tomás en las opiniones de los teólogos dominicos respecto a la cuestión analizada. Se examina la postura negativa y homogénea adoptada por los dominicos, revelando sus fundamentos y la presencia de la perspectiva teológica indicada por santo Tomás de Aquino
La postura de los dominicos ante la cuestión de la Inmaculada Concepción de María a partir del ejemplo de escrituras seleccionadas (siglos XIII-XVI)
Keywords: Thomas Aquinas; Dominicans; Immaculate Conception of Mary; Sanctification of Mary; Authority: Santo Tomás de Aquino; Dominicos; Inmaculada Concepción de María; Santificación de María; Autoridad.